Using advanced wound care and hyperbaric oxygen to manage wound complications following treatment of vulvovaginal carcinoma - C. Griffiths; R.S. Howell; H. Boinpally; E. Jimenez; E. Chalas; F. Musa; S. Gorenstein (Elsevier, 2018)
Postoperative management of patients with vulvar cancer is associated with a high incidence of poor wound healing and radiation -induced late tissue necrosis. This case series demonstrates the impact on wound healing with the use of hyperbaric oxygen therapy and advanced wound care following radical vulvectomy and/or radiation therapy.A retrospective case series was performed of all patients from 2016 to 2017 with lower genital cancer who underwent radical surgery with or without chemoradiation treatment, experienced wound dehiscence or late tissue radionecrosis, and were treated with advanced wound care, including hyperbaric oxygen therapy (HBO).Five patients were included with a mean age of 63; four had squamous cell carcinoma and one patient had vaginal adenocarcinoma secondary to prior diethylstilbestrol exposure. Three patients underwent radical vulvectomy. All received pelvic radiation therapy, subsequently experienced wound complications, and were managed with advanced wound care and HBO. The mean reduction in wound area at the final wound follow up visit after completion of HBO therapy was found to be 76%, ranging 42-95%, with an average follow up of five months. The mean number of HBO sessions per patient was 58. Complete tissue granulation or significant improvement in tissue radionecrosis was present in all patients.Advanced wound care and hyperbaric oxygen therapy are beneficial in the management of postoperative wound complications. Prospective studies are needed to identify the optimal use of perioperative hyperbaric oxygen and appropriate wound care for patients with gynecologic malignancies. Keywords: Hyperbaric oxygen therapy, Radiation tissue necrosis, Vulvar carcinoma